2022
DOI: 10.1177/15691861211073826
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mindfulness parent training on parenting stress and children’s ADHD-related behaviors: A systematic review and meta-analysis

Abstract: Background/Objective Literature shows that there is a circular relationship between children’s ADHD-related behaviors and parenting stress. This systematic review and meta-analysis aimed to understand if mindfulness parent trainings have benefits for both parenting stress and the problem behaviors in children with ADHD. Methods Five databases, CINAHL, Embase, PsycINFO, PubMED, and Web of Science, were searched. Within-group effects at post-treatment and follow-up assessment, and between-group effects at post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(267 reference statements)
0
7
0
Order By: Relevance
“…We also hypothesise a direct effect of the MinUTo intervention on parenting stress, measured in the present study using the Parenting Stress Index Short Form (PSI-SF Italian version [34]). A direct effect of mindful intervention in reducing parenting stress was described in several studies considering parents of children and adolescents with typical and atypical development [8,15]. In our study, we hypothesise a positive effect on the Total Stress global score as well as on Parental Distress and Parent-child Dysfunctional Interaction subscales.…”
Section: Primary Outcomesmentioning
confidence: 56%
See 2 more Smart Citations
“…We also hypothesise a direct effect of the MinUTo intervention on parenting stress, measured in the present study using the Parenting Stress Index Short Form (PSI-SF Italian version [34]). A direct effect of mindful intervention in reducing parenting stress was described in several studies considering parents of children and adolescents with typical and atypical development [8,15]. In our study, we hypothesise a positive effect on the Total Stress global score as well as on Parental Distress and Parent-child Dysfunctional Interaction subscales.…”
Section: Primary Outcomesmentioning
confidence: 56%
“…Several experiences of mindful parenting training and interventions have been proposed for parents of children at risk or with atypical development. Mindfulness training has been offered to parents of children with ADHD, showing positive effects in reducing parenting stress and children's symptoms [8]. Positive effects of mindfulness interventions for parents of children between 3 and 12 years with externalising behaviour were described with decreased parental stress and child problems [9].…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al. (2022) included 10 (five non‐RCTs and five RCTs) studies of children with ADHD and their parents, aiming to evaluate if mindfulness parent training benefits PS. The meta‐analysis included nine of them.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, only one review reported the follow-up results of mindfulness interventions (Lee et al, 2022), which limits the feasibility of this umbrella review to assess the lasting effects of the interventions.…”
Section: Mindfulness Interventionsmentioning
confidence: 99%